Faktor-Faktor Yang Mempengaruhi Ketepatan Kode Diagnosa External Cause Kasus Kecelakaan Sepeda Motor Di RSU Imelda Pekerja Indonesia Medan Tahun 2023 - Simanjuntak, Marta; Christy, Johanna; Erlindai, Erlindai; Berutu, Novita Sari (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2024)
Codefication classification is an activity that groups diseases based on certain. Coding of disease diagnoses must be carried out accurately and completely. The assignment of disease diagnosis codes is in accordance with ICD-10 rules. External cause is a code used to classify the external cause of an illness whwther caused by accidents, injuries, burns, poisoning, side effects of other cause. Factors thar influence the accuracy of external cause diagnosis codes are discrepancies in giving diagnosis codes, erros and discrepancies in giving additional codes for descriptions of activity and place of occurrence. As a passenger or driver, do not include the external cause code in the wxisting diagnosis. This research was conducted at RSU Imelda Pekerja Indonesia Medan with the aim of research to determine the factors that influence the accuracy of the external cause diagnosis code for motorbike accident cases at RSU Imelda Pekerja Indonesia Medan in 2023. This research uses quantitative analytical methods with a cross sectional approch. The research results showed that there was a significant influence of the variable completeness of assessment eith coding accuracy with a value (p value 0.002 < 0,05), there was an influence of completeness of laboratory examination with coding accuracy with a value ( p value 0.045 < 0,05), there was an influence og the quality of code officers according to length of service with value (p value 0.003 < 0,05) and there is an influence on the quality of code officers according to training followed by value (p value 0.017 < 0,05).